A Corpus-Based Cognitive Linguistic Analysis of Taste Words: The Case of English “Bitter” and Chinese Ku (KEMANUSIAAN The Asian Journal of Humanities, 2023)
This study explores the polysemy of the word “bitter” in English and ku in Chinese. It examines the similarities and differences between their semantics and identifies the cognitive mechanisms that motivate their semantic expansion. The study attempts to answer two questions: (1) What are the similarities and differences between Chinese ku and English “bitter” in terms of meaning? (2) What cognitive mechanisms motivate meaning extensions of these two words? To this end, ????? (Chinese Dictionary), ????? (English-Chinese Dictionary), the British National Corpus (BNC) and BLCU Corpus Center (BCC) were employed. The two dictionaries were utilised to investigate the multiple meanings of the two terms, while the BNC and the BCC were employed to identify metaphors and metonymies in sentences. Theoretically, the study is informed by Lakoff and Johnson’s conceptual metaphor and conceptual metonymy. The results showed that half of the meanings of “bitter” and ku overlapped, but there were still some differences. Their semantic expansion is motivated by both conceptual metonymy and conceptual metaphor. In addition, the words under investigation differ in the emotions expressed. English “bitter” is more negative, while Chinese ku is more positive. The present findings have important implications for education and cross-cultural communication in language.